6=k-5

Simple and best practice solution for 6=k-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=k-5 equation:


Simplifying
6 = k + -5

Reorder the terms:
6 = -5 + k

Solving
6 = -5 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
6 + -1k = -5 + k + -1k

Combine like terms: k + -1k = 0
6 + -1k = -5 + 0
6 + -1k = -5

Add '-6' to each side of the equation.
6 + -6 + -1k = -5 + -6

Combine like terms: 6 + -6 = 0
0 + -1k = -5 + -6
-1k = -5 + -6

Combine like terms: -5 + -6 = -11
-1k = -11

Divide each side by '-1'.
k = 11

Simplifying
k = 11

See similar equations:

| -5=h/6 | | 15xz-4y=0 | | 6(p)+4=68 | | (X-4)^3/4 | | -13=7+f | | 5c-10=25 | | (x-4)*7=32 | | 15x^3-20x^5= | | x-4*7=32 | | C+5=-12 | | 5x^4-16x^2+3=0 | | 74=4t+10 | | n*6=80 | | 36=j+13 | | 8y=-10 | | 50+x+30-2=y | | 8+2(x+4)= | | 5n-8=-8 | | (X-5)*8=72 | | (1/2)/(3/5) | | 45*4/9 | | x+35=4 | | (-64)^-2/3 | | 2(7x+7y)=2(-35) | | x^5+5x-36x=0 | | 9(y-2)=8y-6 | | (9x-6w)+(4x+8y)+(4y+4w)= | | -7(2x+2y)=-7(-10) | | n*5=20 | | 0=5p^2+240p-160 | | b/6+3=6 | | X^2+18x+81=21 |

Equations solver categories